Teacher Motivation in Teaching Physical Education During Covid-19 Pandemic - Tri Martini; Mudjihartono; Agus Gumilar; Salman (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2023)
The purpose of this study was to explore the motivation of Junior High School Physical Education teachers in providing online-based Physical Education instruction in Cimahi City, Indonesia. This study used a quantitative descriptive method. The instrument was a questionnaire distributed through Google form. The population of this study were Physical Education teachers in Cimahi. The sampling technique used purposive sampling technique with the Roscoe method. The data were analyzed by quantitative descriptives in the form of percentages. The result of this study concludes that the motivation of Junior High School Physical Education teachers in providing online-based Physical Education teaching in Cimahi are 4.84% were in the high category, 12.90% were in the medium category, 75.81% were in the low category, and 6.54% were in the very low category. It concludes that the teaching motivation of Junior High School level Physical Education teachers in Cimahi, in implementing online learning, was mostly in the low category.